Ergonomics: assessment of sleeping characteristics of part 06 students in Mechanical Engineering UiTM / Mohd Faizal Abdul Hamid, Ridzuan Ahmed and Sulaiman Omar - Abdul Hamid, Mohd Faizal; Ahmed, Ridzuan; Omar, Sulaiman (2001)
Today, in engineering scope the most important thing that should be coincided is "Human Factor in design". Human factor is the study of the interactions between people and the product they use and the environment in that they work and live. Other terms used to describe this field of study are engineering psychology, human engineering, ergonomics, bioengineering and biomechanics. Our final project is related closely to human factor (we classified as ergonomics). The term ergonomics was first coined in England (1949), when Greek word ergon (work) and nomos (study of) were combined to give license to this emerging discipline. Ergonomics defined the scientific study of the relationship between human being and working environment. Ergonomics give comfortable and to avoid the existence of noncomfortable for our work system run effectively and efficiently. Actually ergonomics is not just converge on the design scope only. The management scope also has the ergonomics element that is an organization must provide a systematic and efficiency work schedule for workers to work in comfortable. Lastly, the conclusion of ergonomics is one thing that was very important in today's industries and it is also in daily activity. It was a combination between social science and human factor to achieve management and comfortable in optimum.